HUBUNGAN PENDAPATAN DAN PENDIDIKAN ORANG TUA DENGAN HASIL BELAJAR GEOGRAFI SISWA KELAS XI SMA N 1 ULAKAN TAPAKIS KABUPATEN PADANG PARIAMAN TAHUN PELAJARAN 2021/2022 - Susanti, Cendy; Ahyuni, Ahyuni (JURNAL BUANA, 2023)
This study aims to determine whether there is a relationship between income and parental education on student learning outcomes. This type of research is quantitative with Multiple Linear Regression Method. The population of this research is the students of class XI majoring in Social Studies in the academic year 2021/2022 as many as 80 students with a sample of 80 students using "total sampling". Based on the results of the study, it was concluded that income did not have a positive effect, and education did not have a positive effect on student learning outcomes, while income and parental education simultaneously did not affect student learning outcomes. The results of the calculation of the multiple regression formula between the X_1 variable have a positive value of 1.344 and a significant level of 0.195 > 0.05, meaning that the income variable has no effect. The X_2 variable has a negative value of - 0.215, and a significant level of 0.554 > 0.05, meaning that the education variable has no significant positive effect. The contribution of parents' income and education is only 2.2% to student learning outcomes, while 97.8% is influenced by other factors not examined in this study such as internal factors of interest, talent, motivation, learning methods, and external factors of the school environment, environment its people.